Simmel and Ortega: Relational ontology against the Parmenidean tradition of Being. - Gutiérrez Gutiérrez, Eduardo (Logos. Anales del Seminario de Metafísica, 2022)
In this article, the ontological theories of Georg Simmel and José Ortega y Gasset are compared, with two objectives: to demonstrate the influence of Simmelian vitalism in Ortega’s «ratiovitalism», and to expose their approaches as criticisms of the Parmenídean tradition of Being. The comparative study is carried out based on the thesis of the «intradition of tradition», about which we will say a few words. Finally, we will conclude with the idea that the authors’ ontologies imply a critical review of the ontological implications of the theory of knowledge of modern philosophy.